Framework for OECS trade policy development and management : final report (Dominica Association of Industry & Commerce RoseauDM, 2003)
Seeks to inform the OECS private sector, labour and civil society organizations and government officials on the status of the various external economic trade negotiations i.e. WTO, FTAA and ACP-EU Cotonou Agreement. Focuses on issues that require immediate attention.
Keywords: TRADE POLICY